Lianhao benling suishi zhunbei zhiyuan yuenan, xiaomie meiguo qinlüezhe! - Xu Kuizhi,
'Practice your skills, be prepared at all times, support Vietnam and destroy the American aggressor!' Printno. T8087.2197.